Cyber-crime the challenge in Asia - Broadhurst, Roderic G.; Grabosky, Peter N. 1945- (2005)
This collection is innovative and original. It introduces new knowledge and is very timely because of the current high profile of the international public discourse over security, the internet and its impact upon the growth of the information economy.